MINAT MENGUASAI MATA PELAJARAN EKONOMI PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNTAN - Rohmadayati, Mustika; H. Matsum, Junaidi; Ulfah, Maria (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the interest in mastering economic subjects on the students of Economic Education FKIP Untan. The research method used is descriptive, the research form is survey, and the research approach is quantitative. Respondents of this research document are students of Economic Education program bkk Accounting semester VII PPAPK Force 2014 FKIP Untan and the document is the results of questionnaires and the results of interviews with students of the study program Economic Education bkk Accounting semester VII PPAPK Force 2014. The results showed that the four indicators of interest in mastering economic subject, both for economic material and accounting material into the high category. Can be seen from the results of these studies interest in mastering economic subjects on economic material that is happy feeling of 73,91%, interest of 74,11%, attention of 71,37%, and involvement of 77,84%. And for the results of interest  in mastering economic subjects in the accounting material that is happy feeling of 75,48%, interest of 74,69%, attention of 73,97%, and involvement of 61,31%. Keyword: Interest, Mastering, and Economics Subject